Introduction to JALT’s inaugural special issue (Journal of Applied Learning and Teaching, 2019)
I am very pleased to see this inaugural special issue of JALT being published. May it be the first of many to come! It is a very worthy first special issue that originated in EDU2019, an inspiring, international conference that took place in Athens, Greece, in May this year, and that was organised by the distinguished guest-editors of this issue, Dr Margarita Kefalaki (President of the Communication Institute of Greece) and Dr Fotini Diamantidaki (its Vice-President of Research and Academic Affairs).